2015
DOI: 10.1155/2015/765364
|View full text |Cite
|
Sign up to set email alerts
|

Role of Paricalcitol in Modulating the Immune Response in Patients with Renal Disease

Abstract: Introduction. The aim was to highlight the existence of a relationship between vitamin D deficiency, chronic inflammation, and proteinuria, by measuring neutrophil gelatinase associated lipocalin (NGAL) and common inflammatory markers after administration of paricalcitol, a vitamin D analog, in vivo and in vitro. Methods. 40 patients with end-stage chronic kidney disease (CKD) and secondary hyperparathyroidism and 40 healthy subjects were enrolled. Serum calcium, phosphorus, 25(OH)-vitamin D, parathyroid horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Moreover, vitamin D represses the expression of cyclooxygenase (COX)-2 and upregulates the expression of 15-hydroxyprostaglandin dehydrogenase (15PGDH), the enzyme initiating prostaglandin catabolism, in this way reducing prostaglandin levels and suppressing the production of several proinflammatory cytokines [136,137]. The immunomodulatory action of vitamin D has been well demonstrated also in the study of Lucisano et al [138], where an acute paricalcitol supplementation induced a significant reduction of IL-17, IL-6, IL-1β, TNF-α and IFN-γ in a cohort of CKD patients.…”
Section: Vitamin D and Diabetes In Kidney Diseasesmentioning
confidence: 99%
“…Moreover, vitamin D represses the expression of cyclooxygenase (COX)-2 and upregulates the expression of 15-hydroxyprostaglandin dehydrogenase (15PGDH), the enzyme initiating prostaglandin catabolism, in this way reducing prostaglandin levels and suppressing the production of several proinflammatory cytokines [136,137]. The immunomodulatory action of vitamin D has been well demonstrated also in the study of Lucisano et al [138], where an acute paricalcitol supplementation induced a significant reduction of IL-17, IL-6, IL-1β, TNF-α and IFN-γ in a cohort of CKD patients.…”
Section: Vitamin D and Diabetes In Kidney Diseasesmentioning
confidence: 99%
“…Lucisano et al . found that 25(OH)D 3 can regulate immune processes through down-regulation of IL-17, IL-6, and IFN-γ in cultured human peripheral blood mononuclear cells [ 133 ].…”
Section: Renoprotective Mechanisms Of Vdrmentioning
confidence: 99%
“…However, in one clinical study in patients with vascular inflammation, paricalcitol appeared to exert its effect rather selectively on T-helper cells by interfering with calcineurin-mediated responses [ 36 ]. Modulation of adaptive immune responses in CKD-patients has been demonstrated, reflected by reductions in several inflammatory markers of Th1- Th2 and Th17-responses [ 37 ]. Oblak et al [ 30 ] demonstrated treatment effects in a quite large interventional study of RTRs.…”
Section: Discussionmentioning
confidence: 99%